Digitalisation of the accounting and analytical support service for small businesses - Kraievskyi, Volodymyr Mykolaiovych; Kolisnyk, Olena Pylypivna; Skoryk, Maryna Olehivna; Марина Скорик; Олена Колісник; Володимир Краєвський (Видавничий дім «Гельветика», 2024)
This article examines the impact of digitalisation processes on accounting and analytical technologies for the management of small businesses in the modern economy. It discloses the key aspects of the digital transformation of the accounting profession and provides an analysis of the main software solutions used to automate accounting processes in small enterprises. It also substantiates the importance of integrating digital technologies into accounting practices, which contributes to improving the efficiency of management and control over the financial activities of small businesses. It is established that the ad - vent of digitalisation is transforming conventional methodologies pertaining to management and accounting. The implementation of automated accounting systems has the potential to markedly enhance operational efficiency, curtail the prevalence of routine procedures and mitigate the likelihood of human error. The principal trends of digital transformation are examined, including the transition from physical goods to digital services, the globalisation of local services and the growing significance of digital platforms in facilitating communication between market participants. It is argued that in order to maintain competitiveness, small businesses must not only integrate modern digital tools but also invest in the professional development of their employees, particularly accountants, in order to enhance their ability to work with new information systems. It is determined that the introduction of digital technologies ensures increased transparency of accounting data and its accessibility to key stakeholders of the company, which contributes to the improvement of financial reporting and overall efficiency of management decisions. Special attention is paid to the analysis of popular software products on the Ukrainian market, such as Master: Accounting, Oblik SaaS and ISpro. The functionalities, advantages and disadvantages of each solution are considered, thus allowing an evaluation of their effectiveness in meeting the needs of small businesses. It has been determined that the selection of suitable software is of paramount importance to guarantee the seamless functioning of accounting systems and to attain optimal outcomes in financial management. In light of the findings of the study, recommendations are put forth with the aim of optimising the implementation of digital technologies in small businesses. Furthermore, the crucial importance of adapting to the new business environment brought about by digital transformation is underscored.

У цій статті розглядається вплив процесів цифровізації на бухгалтерський облік і аналітичні технології управління малим бізнесом в сучасній економіці. Розкриває ключові аспекти цифрової трансформації бухгалтерської професії та аналізує основні програмні рішення, які використовуються для автоматизації облікових процесів на малих підприємствах. Також обґрунтовано важливість інтеграції цифрових технологій в бухгалтерську практику, що сприяє підвищенню ефективності управління та контролю за фінансовою діяльністю суб’єктів малого бізнесу. Встановлено, що поява цифровізації трансформує традиційні методології управління та бухгалтерського обліку. Впровадження автоматизованих систем бухгалтерського обліку може помітно підвищити операційну ефективність, скоротити поширеність рутинних процедур і зменшити ймовірність людської помилки. Розглядаються основні тенденції цифрової трансформації, включаючи перехід від фізичних товарів до цифрових послуг, глобалізацію місцевих послуг і зростання значення цифрових платформ для полегшення спілкування між учасниками ринку. Стверджується, що для підтримки конкурентоспроможності малі підприємства повинні не тільки інтегрувати сучасні цифрові інструменти, але й інвестувати в професійний розвиток своїх співробітників, зокрема бухгалтерів, щоб підвищити їх здатність працювати з новими інформаційними системами. Визначено, що впровадження цифрових технологій забезпечує підвищення прозорості облікових даних та їх доступність для ключових стейкхолдерів компанії, що сприяє вдосконаленню фінансової звітності та загалом ефективності управлінських рішень. Особливу увагу приділено аналізу популярних програмних продуктів на українському ринку, таких як Master: Accounting, Oblik SaaS та ISpro. Розглядаються функціональні можливості, переваги та недоліки кожного рішення, що дозволяє оцінити їх ефективність у задоволенні потреб малого бізнесу. Визначено, що вибір відповідного програмного забезпечення є надзвичайно важливим для гарантування безперебійного функціонування систем бухгалтерського обліку та досягнення оптимальних результатів у фінансовому управлінні. У світлі результатів дослідження висуваються рекомендації з метою оптимізації впровадження цифрових технологій у малому бізнесі. Крім того, підкреслюється вирішальна важливість адаптації до нового бізнес-середовища, викликаного цифровою трансформацією.
Keywords: small business; analytical software; digitalisation; software systems; corporate information systems; accounting; малий бізнес; програмне забезпечення; цифровізація; програмні системи; корпоративні інформаційні системи; бухгалтерський облік